2022
DOI: 10.1186/s13690-022-00991-3
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis of patients with COVID-19 admitted at six hospitals in Uganda in 2021: a cohort study

Abstract: Background Assessing factors associated with mortality among COVID-19 patients could guide in developing context relevant interventions to mitigate the risk. The study aimed to describe mortality and associated factors among COVID-19 patients admitted at six health facilities in Uganda. Methods We reviewed medical records of patients admitted with COVID-19 between January 1st 2021 and December 31st 2021 in six hospitals in Uganda. Using Stata versi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 47 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…RT-PCR was used to diagnose COVID-19 in all papers, and RDT and blood smears were the preferred investigations for Malaria diagnosis. Three studies used RT-PCR in addition to blood smear ( Konozy et al, 2022 ; Muyinda et al, 2022 ; Caglar et al, 2021 ). Plasmodium falciparum and vivax were identified as causative types in six studies for each, respectively ( Konozy et al, 2022 ; Guha et al, 2021 ; Huang et al, 2022 ; Boonyarangka et al, 2022 ; Forero-Peña et al, 2022 ; Achan et al, 2022 ; Hussein et al, 2022 ; Scalisi et al, 2022 ; Ahmed et al, 2022 ; Caglar et al, 2021 ; Indari et al, 2021 ; Chen et al, 2021 ), while in three studies, both species were detected ( Lee, Hong & Kim, 2022 ; Muyinda et al, 2022 ; Suarez et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…RT-PCR was used to diagnose COVID-19 in all papers, and RDT and blood smears were the preferred investigations for Malaria diagnosis. Three studies used RT-PCR in addition to blood smear ( Konozy et al, 2022 ; Muyinda et al, 2022 ; Caglar et al, 2021 ). Plasmodium falciparum and vivax were identified as causative types in six studies for each, respectively ( Konozy et al, 2022 ; Guha et al, 2021 ; Huang et al, 2022 ; Boonyarangka et al, 2022 ; Forero-Peña et al, 2022 ; Achan et al, 2022 ; Hussein et al, 2022 ; Scalisi et al, 2022 ; Ahmed et al, 2022 ; Caglar et al, 2021 ; Indari et al, 2021 ; Chen et al, 2021 ), while in three studies, both species were detected ( Lee, Hong & Kim, 2022 ; Muyinda et al, 2022 ; Suarez et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…1.4, CI: 1-2.2, p < 0.01). 28 In different regions of Brazil in 2020 they found a roughly 10% (p < 0.01) increased prevalence of diabetes among patients with COVID-19 compared to those suggesting diabetes could both increase risk of getting COVID-19 and the outcome associated. 37 There are studies that suggest there can be a bitemporal association between diabetes and COVID- The proposed mechanism of diabetes stems beyond just that of COVID-19, but also includes worsening outcomes and increased contraction of upper respiratory infections (URIs).…”
Section: Discussionmentioning
confidence: 97%
“…A National Cohort Study in England with ICU patients found 23% increase in mortality among diabetic patients (hazard ratio [HR]: 1.23, 95% CI: 1.14–1.42, p < 0.01) in 2020 29 . A 2021 survival analysis in Uganda found a 22.5% mortality in COVID‐19 patients hospitalized and 40% higher hazard ratios (HR: 1.4, CI: 1–2.2, p < 0.01) 28 . In different regions of Brazil in 2020 they found a roughly 10% ( p < 0.01) increased prevalence of diabetes among patients with COVID‐19 compared to those suggesting diabetes could both increase risk of getting COVID‐19 and the outcome associated 37 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations